A cluster randomized controlled trial to assess the impact on intimate partner violence of a 10-session participatory gender training curriculum delivered to women taking part in a group-based microfinance loan scheme in Tanzania (MAISHA CRT01): study protocol - Sheila Harvey; Shelley Lees; Gerry Mshana; Daniel Pilger; Christian Hansen; Saidi Kapiga; Charlotte Watts (BMC, 2018)
Abstract Background Worldwide, almost one third (30%) of women who have been in a relationship have experienced physical and/or sexual violence from an intimate partner. Given the considerable negative impacts of intimate partner violence (IPV) on women's physical health and well-being, there is an urgent need for rigorous evidence on violence prevention interventions. Methods The study, comprising a cluster randomized controlled trial (RCT) and in-depth qualitative study, will assess the impact on women's past year experience of physical and/or sexual IPV of a participatory gender training curriculum (MAISHA curriculum) delivered to women participating in group-based microfinance in Tanzania. More broadly, the study aims to learn more about the factors that contribute to women's vulnerability to violence and understand how the intervention impacts on the lives of women and their families. Sixty-six eligible microfinance loan groups are enrolled and randomly allocated to: the 10-session MAISHA curriculum, delivered over 20 weeks (n = 33); or, to no intervention (n = 33). Study participants are interviewed at baseline and at 24 months post-intervention about their: household; partner; income; health; attitudes and social norms; relationship (including experiences of different forms of violence); childhood; and community. For the qualitative study and process evaluation, focus group discussions are being conducted with study participants and MAISHA curriculum facilitators. In-depth interviews are being conducted with a purposive sample of 18 participants. The primary outcome, assessed at 24 months post-intervention, is a composite of women's reported experience of physical and/or sexual IPV during the past 12 months. Secondary outcomes include: reported experience of physical, sexual and emotional/psychological IPV during the past 12 months, attitudes towards IPV and reported disclosure of IPV to others. Discussion The study forms part of a wider programme of research (MAISHA) that includes: a complementary cluster RCT evaluating the impact of delivering the MAISHA curriculum to women not receiving formal group-based microfinance; an economic evaluation; and a cross-sectional survey of men to explore male risk factors associated with IPV. MAISHA will generate rigorous evidence on violence prevention interventions, as well as further insights into the different forms and consequences of violence and drivers of violence perpetration. Trial registration ClinicalTrials.gov ID: NCT02592252, registered retrospectively on 13 August 2015.